Selective Growth of Metal Sulfide, Metal, and Metal-Alloy on 2D CdS Nanoplates - Fridman, Helena; Tian, Liang; Shreteh, Karam; Volokh, Michael; Mokari, Taleb (Frontiers in Materials, 2020)
Two-dimensional CdS-based hybrid nanostructures are intriguing materials with an application prospect in different fields such as sensing (i. e., photoresistors) and solar energy harvesting (photocatalysis, photovoltaics, and so forth). We report herein a colloidal synthetic path for interfacing metal and semiconductor with 2D CdS nanoplates. Selective growth of Au, Pt, and a PtNi alloy as well as Cu2−xS semiconductor is achieved on CdS nanoplates using controlled reduction of metallic precursors and thermal decomposition of a metal-sulfide single-source precursor using standard organic-phase colloidal chemistry.